Nanoscale zero-valent iron application for in situ reduction of hexavalent chromium and its effects on indigenous microorganism populations - Němeček, Jan; Lhotský, Ondřej; Cajthaml, Tomáš (The Science of the total environment, 2014)
Because of its high toxicity and mobility, hexavalent chromium is considered to be a high priority pollutant. This study was performed to carry out a pilot-scale in-situ remediation test in the saturated zone of a historically Cr(VI)-contaminated site using commercially available nanoscale zero-valent iron (nZVI). The site was monitored before and after the nZVI application by means of microbial cultivation tests, phospholipid fatty acid analysis (PLFA) and toxicological tests with Vibrio fischeri. Injection of nZVI resulted in a rapid decrease in the Cr(VI) and total Cr concentrations in the groundwater without any substantial effect on its chemical properties. The ecotoxicological test with V. fischeri did not indicate any negative changes in the toxicity of the groundwater following the application of nZVI and no significant changes were observed in cultivable psychrophilic bacteria densities and PLFA concentrations in the groundwater samples during the course of the remediation test. However, PLFA of soil samples revealed that the application of nZVI significantly stimulated the growth of Gram-positive bacteria. Principle component analysis (PCA) was applied to the PLFA results for the soil samples from the site in order to explain how Cr(VI) reduction and the presence of Fe influence the indigenous populations. The PCA results clearly indicated a negative correlation between the Cr concentrations and the biota before the application of nZVI and a significant positive correlation between bacteria and the concentration of Fe after the application of nZVI.
Keywords: PLFA; nZVI; Soil Pollutants; látky znečišťující půdu; půda; kovové nanočástice; Toxicity; Hexavalent chromium; Indigenous microorganisms; Chromium; Environmental Restoration and Remediation; chrom; půdní mikrobiologie; regenerace a remediace životního prostředí; Bacteria; Soil; Phospholipids fatty acid analysis; Metal Nanoparticles; Soil Microbiology